Qualitative and Quantitative Analysis of Six Fatty Acid Amides in 11 Edible Vegetable Oils Using Liquid Chromatography–Mass Spectrometry - Li, Zixiang; Dong, Feng; Sun, Yongzhi; Sun, Zhaohui; Song, Xinyu; Dong, Yingran; Huang, Xiaocai; Zhong, Jiayi; Zhang, Rui; Wang, Maoqing; Sun, Changhao (Frontiers in Nutrition, 2022)
Fatty acid amides (FAAs) are endogenous lipid molecules that exhibit various physiological activities. FAAs are usually present at nanomolar levels in biological samples. In this study, a method for the qualitative and quantitative determination of six FAAs (linoleamide, linoleoyl ethanolamide, oleoyl ethanolamide, palmitic amide, oleamide, and octadecanamide) in edible vegetable oils was established. All six FAAs were detected in sesame, peanut, soybean (decolorized and non-decolorized), and blended oils; five in sunflower oil; four in rice oil; three in linseed and olive oils; and two in corn and canola oils. The total contents of FAAs were highest in sesame oil (104.88±3.01 µg/mL), followed by peanut oil (34.96±3.87 µg/mL), soybean oil (16.75±1.27 µg/mL), and blended oil (13.33±0.77 µg/mL), and the contents in the other edible vegetable oils were all less than 1.03 µg/mL. The concentrations of linoleoyl ethanolamide and oleoyl ethanolamide were highest in non-decolorized soybean oil, while the other four FAAs (linoleamide, palmitic amide, oleamide, and octadecanamide) showed the highest concentrations in sesame oil. The total contents of these FAAs in eight different oils were higher than those in biological fluids and tissue. Our study confirmed that edible vegetable oils are rich in FAAs, and provides reliable data for evaluating the nutritive value of vegetable oils.